Chromate exposure induces DNA hypermethylation of the mismatch repair gene MLH1 in lung cancer. Issue 1 (3rd October 2019) - Tsuboi, Mitsuhiro; Kondo, Kazuya; Soejima, Shiho; Kajiura, Koichiro; Kawakita, Naoya; Toba, Hiroaki; Kawakami, Yukikiyo; Yoshida, Mitsuteru; Takizawa, Hiromitsu; Tangoku, Akira
Abstract: Hexavalent chromium is recognized as a human carcinogen. Our previous studies revealed that lung cancer (LC) in chromate‐exposed workers (chromate LC) had molecular features of frequent microsatellite instability (MSI), repression of MLH1 level, and aberrant DNA methylation of several tumor‐suppressor genes, including MLH1 . In the present study, we quantitatively investigated MLH1 ‐promoter methylation status using bisulfite pyrosequencing of paired tumorous/nontumorous tissues from chromate and nonchromate LCs to determine the effect of chromate exposure on MLH1 ‐promoter methylation. The methylation level of MLH1 promoter was significantly higher in chromate LC tumors ( P < .001) than nonchromate LC tumors and, among chromate LC, significantly higher in tumorous tissue than nontumorous tissue ( P = .004). Moreover, the methylation level of MLH1 promoter in normal lung tissue tended to be higher in chromate LC than nonchromate LC ( P = .062). In addition, LC with reduced levels of MLH1 showed significantly higher methylation levels of MLH1 promoter than LC exhibiting normal MLH1 levels ( P = .019). Moreover, immunohistochemical analyses determined that levels of SUV39H1, an H3K9me2‐related methyltransferase, were higher in chromate LC than nonchromate LC ( P = .076). Furthermore, we evaluated three DNA double‐strand break‐repair genes ( MRE11, RAD50, and DNA‐PKcs ) as possible targets of MSI by fragment‐length polymorphism analysis, revealing the mutation frequency of RAD50 as significantly higher in chromate LC than nonchromate LC ( P = .047). These results suggest that chromate exposure might induce MLH1 hypermethylation in LC as a mechanism of chromate‐induced carcinogenesis.